OPEN PLATFORM AS A TECHNOLOGICAL BASIS FOR THE DEVELOPMENT OF SBERBANK - A. Berdyshev (Вестник университета)
The article examines the experience of building open platforms by leading global IT companies. The features of the current strategy for transforming the business model of Sberbank, based on the creation of a financial and technological open platform, that ensures interaction with the financial market and other market sectors have identified. Research strategy allows in maximum extent to attract and retain the attention of the client, providing him a «fine-tuning» and personalized targeted offers of financial and non-financial products and services.